20-Hydroxyecdysone activates PGRP-SA mediated immune response in Locusta migratoria. (July 2017) - Han, Pengfei; Han, Jiao; Fan, Jiqiao; Zhang, Min; Ma, Enbo; Li, Sheng; Fan, Renjun; Zhang, Jianzhen
Abstract: 20-hydroxyecdysone (20E) has been implicated in regulating the immune response in insects. Conflicting conclusions on 20E regulating immunity have been reported in model holometabolous species. However, in hemimetabolous insects, the role of 20E as an immune-suppressor or activator and the mechanism remains unclear. The migratory locust Locusta migratoria is a representative member of hemimetabolous insects. Here, digital gene expression (DGE) profiles of Locusta migratoria treated with 20E were analyzed. Pattern recognition receptors [peptidoglycan recognition protein ( PGRP-SA), PGRP-LE, and gram-negative binding protein ( GNBP3 )] and antimicrobial peptides ( defensin, diptericin, and i-type lysozyme ) were significantly induced by 20E in fat body. These immune-related genes significantly increased their mRNA levels during the high-20E stage. Antibacterial activities in plasma were enhanced after 20E injection and during the high-20E developmental stage. Conversely, when 20E signal was suppressed by RNAi of EcR (ecdysone receptor), the expression levels of these genes and antibacterial activities failed to be increased by 20E injection and during the high-20E developmental stage, and the mortality increased after being infected by entomogenous fungus. The knockdown of PGRP-SA inhibited the expression level of defensin, diptericin and i-type lysozyme in fat body and reduced antibacterial activities in plasma. 20E injection could not significantly induce the expression of antimicrobial peptides after RNAi of PGRP-SA . These results demonstrated that 20E enhanced the immune response by activating PGRP-SA in L. migratoria . Graphical abstract: Highlights: In this study, we clarified that 20E activates innate immunity in a representative member of hemimetabolous insects Locusta migratoria. The results demonstrated that 20E activated the innate immune response by binding to the ecdysone receptor in L. migratoria. Our results revealed that 20E controls immune response by regulating PGRP-SA in L. migratoria.